Model Kepemimpinan Kepala Sekolah Dalam Implementasi Kurikulum Merdeka Berbasis Proyek - Agustina Rahmi; Saniyah Saniyah; Dwi Sogi Sri Redjeki; Sabariah Sabariah (LPPM Universitas PGRI Adi Buana Surabaya, 2024)
The principal is the spearhead of the implementation of education in schools. However, in the field it was found that there was still inadequate understanding in the implementation of the Merdeka curriculum and the monitoring and evaluation system was less effective. The aim of this research is to explore the principal's leadership model in implementing the project-based Merdeka curriculum at SDN Sungai Gampa 2, implementation, and identify inhibiting factors and the solutions offered. This research uses qualitative methods with data collection techniques including observation, interviews and documentation. The results of the research show that the leadership model used by the Principal of SDN Sungai Gampa 2, namely: a) implementing transformational leadership, b) opening good communication with parents ensuring the availability of learning resources and encouraging teachers to improve their competence, and d) establishing needs-based policies. Meanwhile, the implementation of the leadership model carried out by the school principal, namely: a) improving the quality of service, b) to teachers, providing support in professional development and providing learning resources, and c) to parents, encouraging teachers to provide information related to child development and efforts to support the Merdeka curriculum. Meanwhile, the solutions taken by the school principal if there are challenges and obstacles are: a) identifying obstacles, b) providing advice and direction, c) evaluating the procurement of needed resources